2018
DOI: 10.1016/j.jbiomech.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic algorithm to determine the energy cost of running with changes of direction

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. KINEMATIC ALGORITHM TO DETERMINE THE ENERGY COST O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…Mechanical energy during a CoD is an indirect measure of its associated metabolic cost. Computed positive/negative external CoM work was in line with previous investigations from different groups [8,16], which ensures the predictions were constructed on a solid basis. The prediction error (1.1–1.4 J) can be considered acceptable as it allows us to get a realistic measure of the amount of energy involved in the braking/propulsive actions, which is highly dependent on running speed.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Mechanical energy during a CoD is an indirect measure of its associated metabolic cost. Computed positive/negative external CoM work was in line with previous investigations from different groups [8,16], which ensures the predictions were constructed on a solid basis. The prediction error (1.1–1.4 J) can be considered acceptable as it allows us to get a realistic measure of the amount of energy involved in the braking/propulsive actions, which is highly dependent on running speed.…”
Section: Discussionmentioning
confidence: 64%
“…The mechanics and neurophysiology of CoDs have been accurately described primarily in laboratory conditions, unveiling joint kinematics and loads as a function of the running angle and technique [1,9,10,11], foot-landing strategies [12], muscular activations [3,13], and response to fatigue [14,15]. In addition, we recently proposed an algorithm to estimate the energy cost of running with repeated 180 degree-CoDs [16]: the external mechanical energy associated to the trajectory of a body’s center of mass was combined with the knee flexion angle and ground contacts to provide an estimation of the positive (concentric) and negative (eccentric) muscular work.…”
Section: Introductionmentioning
confidence: 99%
“…Immediately following the warm-up routine, athletes started the actual exercise protocol, that was extensively described elsewhere (Ciprandi et al, 2018;Zago et al, 2018Zago et al, , 2019 and involved a continuous 5-m shuttle run test designed to induce continuous 180 • turning actions (referred to as changes of direction, CoDs, in the following), repeated with alternated legs to avoid overloading. Running speed was set at an average value of 70% of each participant's maximum aerobic speed (MAS) and it was dictated by a beat counter.…”
Section: Methodsmentioning
confidence: 99%
“…The framework of analysis grounds on repeated turns as those performed in a continuous shuttle run test ( Ciprandi et al, 2018 ; Zago et al, 2018 , 2019 ); 180-degrees changes of direction are sport-specific tasks that can frequently occur during the game ( Jones et al, 2016b ) imply quick decelerations and high breaking forces to redirect the center of mass momentum ( Cortes et al, 2013 ); such forces can be counteracted by either eccentric muscle contractions and/or passive ligaments loading ( Besier et al, 2003 ; Jones et al, 2017 ). While jumps and heading actions were seldom the driver of ACL injuries in football ( Della Villa et al, 2020 ; Lucarno et al, 2021 ), the video analysis of ACL injuries in élite female players revealed that cutting actions like those involved in shuttle run are not only representative of soccer match-play ( Greig, 2009 ), but also a common non-contact injury pattern, especially in defensive “pressing and tackling” situations ( Lucarno et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, sorprendentemente, se han llevado a cabo pocas investigaciones para dilucidar los efectos del entrenamiento de fuerza excéntrico, o el entrenamiento de fuerza con acciones musculares excéntricas, acentuadas en el rendimiento de la velocidad de CoD. Zago, Esposito, Rausa, Rampichini & Sforza (2018), plantean un algoritmo cinemático para determinar el costo energético de correr con cambios de dirección. Los cambios de dirección (CoD) tienen un alto impacto metabólico y mecánico en los deportes de campo y de equipo de la cancha, pero la estimación de la carga de trabajo asociada sigue siendo inexacta.…”
Section: Enfoque Entrenamiento Deportivounclassified